2002
DOI: 10.1034/j.1600-0560.2002.290402.x
|View full text |Cite
|
Sign up to set email alerts
|

Papular xanthoma: a clinicopathological study of 10 cases

Abstract: This series confirms PX as a rare, but distinguished clinicopathologic entity in the spectrum of n-LCH of the skin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 31 publications
0
30
0
1
Order By: Relevance
“…Moreover, no initial nonlipidized histiocytic phase can be traced in the early development of the lesions. Staining for factor XIIIa is negative [1, 2]. In our case, the presence of nonfoamy histiocytes in the early lesion and the importance of the inflammatory infiltrate eliminated this diagnosis.…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, no initial nonlipidized histiocytic phase can be traced in the early development of the lesions. Staining for factor XIIIa is negative [1, 2]. In our case, the presence of nonfoamy histiocytes in the early lesion and the importance of the inflammatory infiltrate eliminated this diagnosis.…”
Section: Discussionmentioning
confidence: 93%
“…The fixed samples were embedded in paraffin according to Sugiyama et al (1992). Xanthelasma histological diagnosis was based on Breier et al (2002) criteria.…”
Section: Methodsmentioning
confidence: 99%
“…[2,4] A series noted positivity for macrophage markers such as KiM1p, CD68, and HAM-56. [7] There are some case reports of PX occurring in association with systemic disorders. Darwin et al have reported a case of generalized PX in a patient with Sezary syndrome.…”
Section: Discussionmentioning
confidence: 98%